The Regional Dimension of North-South Trade-Related R&D Spillovers - Schiff, Maurice (2012)
This paper examines the impact of trade with Japan, North America, and the European Union on technology diffusion and total factor productivity growth in Korea, Mexico, and Jordan. Measures of foreign research and development are constructed based on industry-specific research and development in the North, North-South trade patterns, and input-output relations in the South. The findings show that technology diffusion and productivity gains tend to be regional. Jordan benefits mainly from trade with the European Union, Korea from trade with Japan, and Mexico from trade with North America. In other words, the dynamic version of the "natural trading partners" hypothesis holds for these countries.